H. capsulatum: A Not-So-Benign Cause of Pericarditis. (7th September 2017) - Soriano, Paolo K.; Iqbal, Muhammad; Kandaswamy, Shakthishri; Akram, Sami; Kulkarni, Abhishek; Hudali, Tamer
Abstract : The common causes of pericarditis and its course are benign in the majority of cases. Thus, further testing is usually not pursued and treatment for a presumptive viral etiology with nonsteroidal agents and steroids has been an accepted strategy. We present a patient with pericarditis who was unresponsive to first-line therapy and was subsequently found to have necrotizing granulomas of the pericardium with extensive adhesions and fungal elements seen on tissue biopsy. Serologic testing confirms active H. capsulatum infection, and he responded well to Itraconazole treatment. In patients with pericarditis who fail standard therapy with NSAIDs and steroids, it is suggested that they undergo thorough evaluation and that histoplasmosis be considered as an etiology, especially in endemic regions.